Aplikasi Pemberian Pupuk Kompos Sampah Organik Diperkaya untuk Tanaman Cabe Rawit di Polybag di Kelompok Ibu-Ibu PKK RT 20 Kelurahan Pakuan Baru Kota Jambi - Suryanto; Hasriati Nasution; Sri Mulyati; Asmadi Saat (Studium: Jurnal Pengabdian Kepada Masyarakat, 2025)
Bird’s eye chili (Capsicum frutescens) is an agricultural commodity with several advantages, including tolerance to climate variability, relatively high resistance to pests and plant diseases, and high productivity. Nevertheless, this crop requires growing media rich in nutrients, one of which can be provided through the use of enriched organic waste compost. Enriched organic waste compost is produced through the decomposition of plant and animal residues with the assistance of decomposer organisms, including both microorganisms and macroorganisms. This community service activity aimed to enhance the skills of members of the PKK women’s group of RT 20, Pakuan Baru Subdistrict, Jambi City, in cultivating bird’s eye chili to achieve healthy growth and high fruit yield. The outreach activities were conducted in two stages, namely the delivery of educational materials and hands-on practice. Following the implementation of the training, an improvement in participants’ knowledge was observed, and they were able to apply enriched organic waste compost in their cultivation practices.